Metode problem based learning dalam mengembangkan pemikiran kritis siswa kelas 7 di MTS al-Ma’arif 03 Singosari - Oktarina, Amalia Eka (Maliki Interdisciplinary Journal, 2024)
This article focuses on the subject of Social Studies (IPS) and how education plays a significant role in improving students’ critical thinking skills in the 21st century. Considered important, learning IPS provides direct insight into social phenomena such as geography and economics. It is expected that teachers can create a challenging learning environment that helps students learn to think critically. Problem-Based Learning (PBL), which aims to improve students’ understanding of concepts through solving real-world problems, is one of the learning approaches promoted. This study was conducted through a descriptive qualitative approach and data were collected through observation, interviews, and questionnaires. Data were analyzed using the Miles and Huberman model. The results showed that problem-based learning is effective in improving students’ critical thinking skills. However, students face challenges such as lack of supporting facilities and low student interest in IPS.